PENGARUH KINERJA TERHADAP KUALITAS PELAYANAN PADA DINAS KEPENDUDUKAN DAN PENCATATATN SIPIL KABUPATEN MAMUJU UTARA - Makkasau, Juhria (Katalogis, 2016)
The aim of this study; (1) Great to know simultaneously influence the performance of the quality of service in the Department of Population and Civil Registration of North Mamuju regency; (2) untukmengetahuibesar partial effect on the performance quality of service at the Department of Population and Civil Registration of North Mamuju regency. Theory of performance used from T.R. Mitchell in Sedarmayanti (2009: 51), while the service quality theory of Parasuraman et al. (1988: 23) This type of research inikuantitatifdenganpendekatan survey. This study population pegawaidan society, in which 32 people while the number of employees totaled 45 796 community mental drawn using formulas to 100 people. Employees using census sampling, while for people to use simple random sampling, and data analysis techniques using multiple linear regression. The results showed; (1) The effect of simultaneous performance of the quality of service in the Department of Population and Civil Registration Mamuju Utara determined by the dimensions of quality of work (quality of work), promptness (timeliness), initiative (initiative), capability (ability), communication (communication) because the calculated F value is greater than the value of F table with a big influence 87.2% with the level of relations between variables are very kuat.Artinya if the performance increase of the unit, it will improve the quality of service; (2) The effect of partial performance of the quality of service in the Department of Population and Civil Registration of North Mamuju regency is determined by the quality of work (quality of work) significantly affects the quality of service for the value of t is greater than t table. Promptness (timeliness) significantly affects the quality pelayanankarena t value greater than t table. Initiative (initiative) significantly affects the quality pelayanankarena t value greater than the value t tabel.Capability (ability) significantly affects the quality pelayanankarena t value greater than t table, and communication (communication) significantly affects the quality pelayanankarena value of t count is greater than t table.